IMPLEMENTATION OF WEB-TECHNOLOGIES IN THE PROCESS OF TEACHING FOREIGN LANGUAGES (Archive of Conferences, 2020)
In this scientific article recent methods and information technologies of teaching the English language at a higher educational institution are analyzed. in this day and age university teachers use a range of interactive technologies in the process of teaching foreign languages in order to make practical lessons more interesting and informative, as well as to increase the motivation of students to study foreign languages.